Existence of Linear Equilibria in the Kyle Model with Multiple Informed Traders - Georg Nöldeke; Thomas Tröger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
We consider Kyle's market order model of insider trading with multiple informed traders and show: if a linear equilibrium exists for two different numbers of informed traders, asset payoff and noise trading are independent and have finite second moments, then these random variables are normally distributed.
Keywords: C62; D82; G14; 330; insider trading; Kyle model; linear equilibrium; normal distribution